Perineuronal nets affect memory and learning after synapse withdrawal - Ruzicka, Jiri; Dalecka, Marketa; Safrankova, Kristyna; Peretti, Diego; Jendelova, Pavla; Kwok, Jessica C F; Fawcett, James W (Translational psychiatry, 2022)
Perineuronal nets (PNNs) enwrap mature neurons, playing a role in the control of plasticity and synapse dynamics. PNNs have been shown to have effects on memory formation, retention and extinction in a variety of animal models. It has been proposed that the cavities in PNNs, which contain synapses, can act as a memory store and that they remain stable after events that cause synaptic withdrawal such as anoxia or hibernation. We examine this idea by monitoring place memory before and after synaptic withdrawal caused by acute hibernation-like state (HLS). Animals lacking hippocampal PNNs due to enzymatic digestion by chondroitinase ABC or knockout of the PNN component aggrecan were compared with wild type controls. HLS-induced synapse withdrawal caused a memory deficit, but not to the level of untreated naïve animals and not worsened by PNN attenuation. After HLS, only animals lacking PNNs showed memory restoration or relearning. Absence of PNNs affected the restoration of excitatory synapses on PNN-bearing neurons. The results support a role for hippocampal PNNs in learning, but not in long-term memory storage for correction of deficits.
Keywords: Learning; extracelulární matrix; Animals; Extracellular Matrix; Extracellular Matrix Proteins; synapse; Neurons; zvířata; Synapses; učení; extracelulární matrix - proteiny; neurony